Small and Medium Enterprises in Algeria - Between economic importance and environmental Challenges - Aboubaker BOUSSALEM; Atallah BEN TAIRECHE) (Journal of Excellence for Economics and Management Research, 2017)
The aim of this paper is to explore and increase the understanding of the role of SMEs in their overall development (economic, social and environmental), and its impact on the national economy and to develop an objective vision of the axes that can be derived from them in order to find ways to increase their productive efficiency in order to expand their contribution to development and to explore the best means that can be used to ensure optimal development.     The study found that the environmental interest of small and medium enterprises can ultimately achieve a competitive advantage to ensure its survival and sustainability in the business environment.